Effects of nutritional and anti-nutritional properties of seeds on the feeding ecology of seed-eating birds of the Monte desert, Argentina - Rios, Juan Manuel (2012)
Food quality and physiological capacities and limitations in recognizing and processing food are among the factors influencing the choices of desert birds in feeding. Seed-eating birds of the central Monte desert generally select grass seeds rather than forb seeds. We studied some of the mechanisms underlying seed-selection patterns in seed-eating birds of the Monte desert, analyzing nutrients and secondary compounds of the 15 most abundant seeds in the soil and their relationship with the diet of six species of seed-eating birds. Grass seeds contained more starch and less total phenols than did forb seeds and were free from alkaloids. The diet of the most graminivorous birds was correlated with seeds' starch concentration, while generalists' diet was correlated with seed abundance. To assess the plausible mechanisms underlying birds' selection of seed, we experimented with three species differing in the breadth of their diet: a generalist, the Rufous-collared Sparrow (Zonotrichia capensis), and two graminivores, the Many-colored Chaco-Finch (Saltatricula multicolor) and Common Diuca-Finch (Diuca diuca). We postulated that the level of starch and the presence of phenolic compounds and alkaloids influence food preference. Results suggest that most graminivorous birds prefer high-starch diets and avoid diets with phenols and alkaloids. In contrast, the generalist foraged regardless of starch content, and its food intake was reduced only by some of the phenols and alkaloids tested. Seed chemistry may explain some important features of seed selection by birds in the Monte desert. © The Cooper Ornithological Society 2012.